Enhancing English Vocabulary Learning for Students with Autism Spectrum Disorder through the Learn English for Kids Application - Oktaviani, Diana; Susanto, Susanto; Nanda, Deri Sis (JOLIES : Journal of Linguistic and English Studies, 2026)
Autism Spectrum Disorder (ASD) is a developmental condition that affects communication, social interaction, and behavior, often making language learning more challenging. As a result, language teaching programs for students with autism must be designed differently from those created for typically developing learners. Most autistic learners are visual thinkers who acquire knowledge more effectively through images and visual aids. To support this need, an application called Learn English for Kids was developed to help children with autism learn English vocabulary. This study examines the use of the Learn English for Kids application as a tool for teaching English vocabulary to students with ASD. A qualitative descriptive method was employed at SLB Yamet School Cendana Lampung, involving five male students diagnosed with autism. The findings indicate that integrating visual and auditory features within the application creates a stimulating and supportive learning environment that aligns with the learning characteristics of children with autism. The use of reinforcement enhances engagement and comprehension, although challenges such as limited attention span and mood fluctuations persist. Combining digital media with behavioral strategies offers an effective framework for inclusive language instruction.